The effects of various beverages on the shear bond strength of light-cured orthodontic composite (An in vitro comparative study) - Mohammed Nahidh (College of Dentistry/ University of Baghdad, 2014)
Background: This study was conducted to assess the effects of various beverages on the shear bond strength of light-cured orthodontic composite used to bond stainless steel orthodontic brackets on human teeth and to determine the site of bonding failure of this material. Materials and Methods: Fifty extracted human premolars were selected and randomly divided into five equal groups each with 10 teeth according to the beverage type (Control, One Tiger, Milk, Green tea and Coffee). After bonding, the teeth were immersed in specific beverages for 5 minutes twice daily with equal intervening intervals then washed and stored in distilled water at 37º C for the reminder of the day. The process was carried out for 30 days. The samples were then tested for shear bond strength using Tinius-Olsen testing machine with a crosshead speed of 0.5mm/minute. For adhesive remnant index, the enamel surface and bracket base of each tooth were inspected under magnifying lens (20X) of a stereomicroscope. Results: Milk, coffee and one Tiger energy drink reduced the shear bond strength of the light-cured composite significantly unlike the green tea. The predominant site of bond failure was between the bracket base and the adhesive leaving the composite on the tooth rather on the brackets base. Conclusions: Orthodontic patients should be instructed to reduce the intake of acidic and fatty beverages to prevent debonding of the orthodontic brackets.